(untitled) (African Journal of Geographical Science, 2020)
This study analyzed the spatial distribution of tricycle stations in Kaduna North Local Government Area, Kaduna state. Specifically the study mapped tricycle stations, the spatial pattern of the tricycle stations and the major areas of influence or service of each tricycle stations. The study used the coordinates of tricycle stations in Kaduna North L.G.A, data generated from structured and validated questionnaires administered to the tricycle operators in each of the nineteen (19) stations distributed within Kaduna North L.G.A and the movement of tricyclist to and from the stations. Focus group discussion with the station operator’s leaders was also adopted to generate data on factors influencing positioning/sitting of the stations. The methods of data analysis used were nearest neighbor analysis and creation of buffers to map the major areas of influence of each tricycle station. Findings from the study revealed that Ahmadu Bello Way had the highest number of tricycle stations with seven (7) stations and that the spatial distribution pattern between the tricycle stations is random pattern. Fourteen (14) of the tricycle stations were located along the major roads. The factors responsible for the location of the tricycle stations vary from one station to another and from one area to another, but most of them had one factor in common, which is, most of the tricycle stations were also stations for buses, taxis or bus stops. Findings also revealed that 46.05% of the operators were in the tricycle business because of the ban on Okada by the Kaduna State Government. As such, Okada operators were converted to tricycle operators; while unemployment, family sustenance and business failure were also part of the reasons why the operators ventured into the tricycle operation. The study recommended that state and local governments should provide a good road transport network and an organized mass transit system to help the tricycle system to provide a more efficient integrated public transport system in the study area.